Underexpression of LINC00173 in TCF3/PBX1-Positive Cases Is Associated With Poor Prognosis in Children With B-Cell Precursor Acute Lymphoblastic Leukemia - Didier Ismael May-Hau; Didier Ismael May-Hau; Diego Alberto Bárcenas-López; Diego Alberto Bárcenas-López; Juan Carlos Núñez-Enríquez; Vilma Carolina Bekker-Méndez; Fredy Omar Beltrán-Anaya; Elva Jiménez-Hernández; Mónica Patricia Ortíz-Maganda; Francisco Xavier Guerra-Castillo; Aurora Medina-Sanson; Janet Flores-Lujano; et al. (Frontiers in Oncology, 2022)
BackgroundB-cell precursor acute lymphoblastic leukemia (BCP-ALL) is the most frequent pediatric cancer worldwide. Despite improvements in treatment regimens, approximately 20% of the cases cannot be cured, highlighting the necessity for identifying new biomarkers to improve the current clinical and molecular risk stratification schemes. We aimed to investigate whether LINC00173 is a biomarker in ALL and to explore its expression level in other human cancer types.MethodsA nested case–control study including Mexican children with BCP-ALL was conducted. LINC00173 expression was evaluated by qRT-PCR using hydrolysis probes. To validate our findings, RNA-seq expression data from BCP-ALL and normal tissues were retrieved from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) and Genotype-Tissue Expression (GTEx) repositories, respectively. LINC00173 expression was also evaluated in solid tumors by downloading available data from The Cancer Genome Atlas (TCGA).ResultsA lower expression of LINC00173 in BCP-ALL cases compared to normal subjects was observed (p < 0.05). ALL patients who carry the TCF3/PBX1 fusion gene displayed lower expression of LINC00173 in contrast to other BCP-ALL molecular subtypes (p < 0.04). LINC00173 underexpression was associated with a high risk to relapse (HR = 1.946, 95% CI = 1.213–3.120) and die (HR = 2.073, 95% CI = 1.211–3.547). Patients with TCF3/PBX1 and underexpression of LINC00173 had the worst prognosis (DFS: HR = 12.24, 95% CI = 5.04–29.71; OS: HR = 11.19, 95% CI = 26–32). TCGA data analysis revealed that underexpression of LINC00173 is also associated with poor clinical outcomes in six new reported tumor types.ConclusionOur findings suggest that LINC00173 is a biomarker of poor prognosis in BCP-ALL and other types of cancer. We observed an association between the expression of LINC00173 and TCF3/PBX1 and the risk to relapse and die in BCP-ALL, which is worse in TCF3/PBX1-positive cases displaying underexpression of LINC00173. Experimental studies are needed to provide insight into the LINC00173 and TCF3/PBX relationship.